Allelic variation in Puroindoline genes in synthetic hexaploid wheats and development of allele-specific PCR markers for new soft-texture alleles - Khan, Muhammad Aamir; Yuanyuan Tian; Humaira Qayyum; Awais Rasheed; He Zhonghu (Springer, 2024)
Grain hardness is an important end-use quality trait which can significantly affect milling and processing quality of wheat. It is controlled by Puroindoline (Pin) genes in wheat, of which Pina-D1 and Pinb-D1 control major phenotypic variation, while Pinb-B2 explain moderate variation. We analyzed the allelic variation of three Pin genes in a panel of 227 synthetic hexaploid wheats (SHWs) using allele-specific markers either previously available or newly developed in this study to identify new alleles and facilitate their introgression. Eight different alleles were identified in Pina-D1 gene using six newly developed markers. The wild-type alleles, Pina-D1a and Pinb-D1a, were identified in 11.6 and 24.2% of accessions, respectively. It was found that Pina-D1c was most frequent (30.7%), followed by Pina-D1e allele (18%) at Pina-D1. For Pinb-D1, three new markers were developed which classified synthetic wheats into four haplotype groups, of which Hap-IV (Pinb-D1j/Pinb-D1o) was most frequent (52.8%). A cleaved amplified polymorphic site (CAPS) marker using ApoI restriction enzyme successfully classified accessions into wild-type and non-wild-type groups. At Pinb-B2 gene, the frequency of Pinb-B2b allele was higher (76.2%) which is associated with relatively hard texture compared to Pinb-B2a allele. The results provide a deeper insight into the allelic composition of grain of grain texture genes in SHWs which can be introgressed to develop required texture market class using allele-specific markers developed in this study.